Corporate Governance and Earnings Management: The Impact of Board Independence and Audit Committee Effectiveness - Fitri Nurjanah; Bandi; Payamta; Jaka Winarna (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to explain the influence of independent board of commissioners and audit committee effectiveness on real earnings management. The population of this study is manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) for the period 2015-2022. The sampling technique used in this study is purposive sampling, namely a sampling technique with certain considerations or criteria. The data analysis technique used is descriptive statistical testing and multiple regression using data processing software. The findings reveal that both the independence of the board of commissioners and the effectiveness of the audit committee play a significant role in mitigating real earnings management. Specifically, these governance mechanisms are shown to have a negative and statistically significant influence on the extent to which firms engage in real earnings management.